Wood production and biodiversity conservation are rival forestry objectives in Europe's Baltic Sea Region. Issue 3 (6th March 2018) - Angelstam, Per; Naumov, Vladimir; Elbakidze, Marine; Manton, Michael; Priednieks, Janis; Rendenieks, Zigmars
Abstract: The policy term green infrastructure highlights the need to maintain functional ecosystems as a foundation for sustainable societies. Because forests are the main natural ecosystems in Europe, it is crucial to understand the extent to which forest landscape management delivers functional green infrastructures. We used the steep west–east gradient in forest landscape history, land ownership, and political culture within northern Europe's Baltic Sea Region to assess regional profiles of benefits delivered by forest landscapes. The aim was to support policy‐makers and planners with evidence‐based knowledge about the current conditions for effective wood production and biodiversity conservation. We developed and modeled four regional‐level indicators for sustained yield wood production and four for biodiversity conservation using public spatial data. The western case study regions in Sweden and Latvia had high forest management intensity with balanced forest losses and gains which was spatially correlated, thus indicating an even stand age class distribution at the local scale and therefore long‐term sustained yields. In contrast, the eastern case study regions in Belarus and Russia showed spatial segregation of areas with forest losses and gains. Regarding biodiversity conservation indicators, the west–east gradient was reversed. In the Russian, Belarusian, and Latvian case study regions, tree species composition was more natural than in Sweden, and the size of contiguous areas without forest loss was larger. In all four case study regions, 54–85% of the total land base consisted of forest cover, which is above critical fragmentation thresholds for forest landscape fragmentation. The results show that green infrastructures for wood production and biodiversity conservation are inversely related among the four case study regions, and thus rival. While restoration for biodiversity conservation is needed in the west, intensified use of wood and biomass is possible in the east. However, a cautious approach should be applied because intensification of wood production threatens biodiversity. We discuss the barriers and bridges for spatial planning in countries with different types of land ownership and political cultures and stress the need for a landscape approach based on evidence‐based collaborative learning processes that include both different academic disciplines and stakeholders that represent different sectors and levels of governance.